Validation of the Ludwigshafen German version of the Burn Specific Health Scale-Brief - Stolle, Annette M.; Magdanz, Janina; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of burn care & research, 2018)
The Burn Specific Health Scale-Brief (BSHS-B) is one of the most commonly used instruments to measure quality of life after burns. Our aim was to establish and to provide a German version of the BSHS-B for all German-speaking burn facilities. Translation and cross-cultural adaptation of the original English version into the German language was conducted. In a pilot study, 20 burn patients qualitatively validated the translated version concerning comprehensibility and content validity. The final version was then quantitatively validated by 364 patients who were treated in our burn center between 2011 and 2015. Internal consistency and test-retest reliability were assessed. Criterion validity was determined by correlating the subscales with relevant instruments (Short-Form Health Survey 36, Hospital Anxiety and Depression Scale, and Disabilities of the Arm, Shoulder and Hand Outcome Measure). The structure of the German version was investigated by principal component analysis. Confirmatory factor analysis was used to compare the structure with the original 9-factor structure and the second-order 3-factor structure. Qualitative testing revealed adequate comprehension and content validity. Cronbach’s alphas ranged from α = 0.80 to α = 0.92. The test-retest reliability ranged from r = 0.72 to r = 0.97. The subscales correlated significantly with the measures of criterion validity (r = 0.30 to r = -0.77). The principal component analysis results showed a satisfactory overlap with the original data structure, except for the Affect and Sexuality domains, which were merged into 1 factor. The confirmatory factor analyses revealed the best model fit for the second-order 3-factor structure, excluding the Work domain. The Ludwigshafen German version of the BSHS-B shows good psychometric properties. It is well suited for clinical use, further research, and international comparison.
Gesehen am 15.09.2019